Adoptive regulatory T cell therapy preserves systemic immune homeostasis following cerebral ischemia - Li, Peiying (2013)
BACKGROUND AND PURPOSE: Cerebral ischemia has been shown to result in peripheral inflammatory responses followed by long-lasting immunosuppression. Our recent study demonstrated that intravenous delivery of Tregs markedly protected against transient cerebral ischemia by suppressing neutrophil-derived matrix metallopeptidase-9 production in the periphery. The impact of Tregs on systemic inflammatory responses and immune status, however, have not been fully characterized. METHODS: Cerebral ischemia was induced by middle cerebral artery occlusion (MCAO) for 60 minutes in mice or 120 minutes in rats. Tregs were isolated from donor animals by CD4 and CD25 double selection and transferred intravenously to ischemic recipients at 2 hours after MCAO. Animals were sacrificed on different days after reperfusion. The effects of Tregs on systemic inflammation and immune status were evaluated using flow cytometry, ELISAs, and immunohistochemistry. RESULTS: Systemic administration of purified Tregs raises functional Tregs in the blood and peripheral organs, including spleen and lymph nodes. These exogenous Tregs remain in the blood and peripheral organs for at least 12 days. Functionally, Treg adoptive transfer markedly inhibits MCAO-induced elevation of inflammatory cytokines (IL-6 and TNF-α) in the blood. Furthermore, Treg treatment corrects long-term lymphopenia and improves cellular immune functions after ischemic brain injury. As a result, Treg-treated animals exhibit decreased bacterial loads in the blood during the recovery from cerebral ischemic attack. CONCLUSIONS: Treg treatment did not exacerbate post-stroke immunosuppression. On the contrary, Treg-treated animals displayed improved immune status after focal cerebral ischemia.